Access to timely formal dementia care in Europe: protocol of the Actifcare (ACcess to Timely Formal Care) study. Issue 1 (December 2016) - Kerpershoek, Liselot; de Vugt, Marjolein; Wolfs, Claire; Jelley, Hannah; Orrel, Martin; Woods, Bob; Stephan, Astrid; Bieber, Anja; Meyer, Gabriele; Engedal, Knut; Selbaek, Geir; Handels, Ron; et al.
Abstract Background Previous findings indicate that people with dementia and their informal carers experience difficulties accessing and using formal care services due to a mismatch between needs and service use. This mismatch causes overall dissatisfaction and is a waste of the scarce financial care resources. This article presents the background and methods of the Actifcare (ACcess to Timely Formal Care) project. This is a European study aiming at best-practice development in finding timely access to formal care for community-dwelling people with dementia and their informal carers. There are five main objectives: 1) Explore predisposing and enabling factors associated with the use of formal care, 2) Explore the association between the use of formal care, needs and quality of life and 3) Compare these across European countries, 4) Understand the costs and consequences of formal care services utilization in people with unmet needs, 5) Determine the major costs and quality of life drivers and their relationship with formal care services across European countries. Methods In a longitudinal cohort study conducted in eight European countries approximately 450 people with dementia and informal carers will be assessed three times in 1 year (baseline, 6 and 12 months). In this year we will closely monitor the process of finding access to formal care. Data on service use, quality of life and needs will be collected. Discussion The results of Actifcare are expected to reveal best-practices in organizing formal care. Knowledge about enabling and predisposing factors regarding access to care services, as well as its costs and consequences, can advance the state of the art in health systems research into pathways to dementia care, in order to benefit people with dementia and their informal carers.